Stability and Change in Posttraumatic Distress: A 7‐Year Follow‐Up Study of Mothers and Young Children Exposed to Cumulative Trauma. Issue 2 (13th April 2017) - Pat‐Horenczyk, Ruth; Cohen, Sarale; Ziv, Yuval; Achituv, M.; Brickman, Sophie; Blanchard, Tamar; Brom, Danny
Abstract : In situations of cumulative trauma, it is often unclear why some people remain resilient, whereas others experience distress, and how likely these responses are to change over time. To investigate the constancy of responses to cumulative trauma, stability and change in posttraumatic distress and resistance (as defined by no evidence of clinical symptoms) were assessed twice in 140 Israeli children and mothers exposed to continual rocket attacks over approximately 7 years, when the children were 2–4 (Time 1) and 9–11 years of age (Time 2). Measures included trauma exposure, posttraumatic and depressive symptoms, and child behavioral problems. We identified 4 longitudinal courses (LCs): resilient (resistance at Time 1 and Time 2), recovered (clinical distress at Time 1 and resistance at Time 2), developed symptoms (resistance at Time 1 and clinical distress at Time 2), and chronic distress (clinical distress at Time 1 and Time 2). Results showed more stability than change in the frequencies of resistance at both times of measurement. The resilient LC was the most common longitudinal course for both mothers and children. Multinomial regression models indicated that maternal posttraumatic symptoms predicted the recovered and chronic distress LCs of the children.